Energy supplementation for beef steers grazing tropical grass (Brachiaria brizantha, cv Marandu) managed under rotational system with different initial sward heights - Dorea, João Ricardo Rebouças (2014)
Two trials were conducted simultaneously to evaluate the effects of energy supplementation for cattle grazing tropical pastures managed with different initial sward heights on DMI and ruminal fermentation of cattle grazing intensively managed tropical grass during the rainy season. Eight 24-month-old rumen-cannulated Nellore steers were used per trial (Trial 1: 300 kg BW ± 5.97, Trial 2: 343 kg BW ± 7.40) allocated in two 4x4 Latin squares. Treatments corresponded to 0 (mineral supplementation) and a 0.3 (0.3% of BW of ground corn as fed basis) combined with 2 pre-grazing sward heights (25 and 35 cm). The stubble height was 15 cm. In the second trial the level of supplementation was 0.6% BW of ground corn as fed basis. Steers were managed in 2 ha of Palisadegrass pasture (Brachiaria brizantha marandu). Pastures were fertilized with 120 kg nitrogen/ha and averaged 13.8 and 11.0% CP and 58.8 and 63.4% NDF, for 25 and 35 cm, respectively The forage and the diet DM and CP digestibility were greater (P<0.05) for 25 then for 35 cm grazing management. For both trials 1 and 2, cattle grazing the pastures with 25 cm initial sward height consumed more forage DMI, more total DMI and more energy (P<0.05) and at the same time steers spent less time grazing (P<0.05) and more time resting (P<0.05), presented greater bite rates (P<0.05), less steps per day and less steps between feeding stations (P<0.05), when compared with cattle grazing the 35 cm pastures. Rumen pH values were less (P<0.05 in trial 1; P<0.1 in trial 2) and concentrations of rumen N-NH3 and retention of N were greater (P<0.05) for cattle grazing the 25 cm pastures while rumen VFA and microbial synthesis were not affected (P>0.05) by pasture management. Supplementing energy at 0.3% (trial 1) increased (P<0.05) diet DM digestibility while feeding energy at 0.6% (trial 2) decreased forage CP digestibility, increased (P<0.05) forage NDF digestibility and increased diet DM (P<0.05) and diet NDF (P<0.1) digestibility. Supplementing energy at 0.3% (trial 1) or at 0.6% (trial 2) decreased forage DMI (P<0.05) and substitution rates were 1.63 and 0.72, respectively. The total DMI and energy intake were not increased (P>0.05) by supplementing energy at 0.3% while increasing energy supplementation to 0.6% was effective to increase total DMI and energy intake of cattle grazing tropical forage, independent of initial sward height. Energy supplementation decreased (P<0.05) grazing time, but it did not affect (P>0.05) any other grazing behavior parameter. Supplementing grazing cattle with 0.3% had no effect (P>0.05) on rumen pH, N retention and microbial synthesis, increased (P<0.05) rumen propionate and decreased (P<0.05) rumen N-NH3, rumen acetate and acetate:propionate ratio. Supplementing grazing cattle with 0.6% decreased (P<0.05) rumen pH, rumen N-NH3, rumen acetate and acetate:propionate ratio, while it increased (P<0.05) rumen propionate, N retention and microbial synthesis. Plasma glucose was not affected by treatments (P>0.05). The pre-grazing sward height of 25 cm and feeding energy supplement at 0.6% of BW were efficient strategies to increase energy intake of cattle grazing Palisadegrass.